The Effect of Picture and Picture Learning Model towards Science Outcomes for Students with Hearing Impairment in the Class VII - Yaumil Ainin Pradina; Wiwik Dwi Hastuti (Department of Special Education, 2017)
Learning science would be difficult if it is abstract. This impact on students’ learning outcomes, because it make learning activity not absorbed maximally. It happens to all students including students with hearing impairment. The purpose of this study was to know the effect of the picture and picture learning model towards science learning outcomes. This research was quasi-experimental (Quasi Experiment) with the type of time series design. The results showed that there are significant differences between the average value of pretest and post-test. It can be concluded that the learning model picture and picture effected the science learn outcomes for students with hearing impairment in SMPLBN